Yeast's balancing act between ethanol and glycerol production in low‐alcohol wines. Issue 2 (13th January 2017) - Goold, Hugh D.; Kroukamp, Heinrich; Williams, Thomas C.; Paulsen, Ian T.; Varela, Cristian; Pretorius, Isak S.
Summary: Alcohol is fundamental to the character of wine, yet too much can put a wine off‐balance. A wine is regarded to be well balanced if its alcoholic strength, acidity, sweetness, fruitiness and tannin structure complement each other so that no single component dominates on the palate. Balancing a wine's positive fruit flavours with the optimal absolute and relative concentration of alcohol can be surprisingly difficult. Over the past three decades, consumers have increasingly demanded wine with richer and riper fruit flavour profiles. In response, grape and wine producers have extended harvest times to increase grape maturity and enhance the degree of fruit flavours and colour intensity. However, a higher degree of grape maturity results in increased grape sugar concentration, which in turn results in wines with elevated alcohol concentration. On average, the alcohol strength of red wines from many warm wine‐producing regions globally rose by about 2% (v/v) during this period. Notwithstanding that many of these 'full‐bodied, fruit‐forward' wines are well balanced and sought after, there is also a significant consumer market segment that seeks lighter styles with less ethanol‐derived 'hotness' on the palate. Consumer‐focussed wine producers are developing and implementing several strategies in the vineyard and winery to reduce the alcohol concentration in wines produced from well‐ripened grapes. In this context, Saccharomyces cerevisiae wine yeasts have proven to be a pivotal strategy to reduce ethanol formation during the fermentation of grape musts with high sugar content (> 240 g l −1 ). One of the approaches has been to develop 'low‐alcohol' yeast strains which work by redirecting their carbon metabolism away from ethanol production to other metabolites, such as glycerol. This article reviews the current challenges of producing glycerol at the expense of ethanol. It also casts new light on yeast strain development programmes which, bolstered by synthetic genomics, could potentially overcome these challenges. Abstract : This article reviews the current challenges of producing glycerol at the expense of ethanol in wine yeast fermentation.